Investigating the effect of zinc supplementation on preventing bone resorption in a weightlessness animal model: An experimental study - Reza Eslami; Amir Khoshvaghti; Kamyab Alizadeh (فصلنامه ابن سینا)
Background and aims: Bone biomarkers, such as bone-specific alkaline phosphatase (BAP) and osteocalcin (OC), are crucial for researching and monitoring the effects of therapeutic interventions. This study aimed to investigate the impact of oral zinc supplementation on BAP and OC levels in a weightlessness simulation model in rats. Methods: In this experimental study with a control group, 14 male Wistar rats were subjected to simulated weightlessness through tail suspension. The rats were divided into intervention (receiving oral zinc sulfate) and control groups. Serum levels of BAP and OC were measured at the beginning and end of a 30-day period. Results: Life in a weightless environment resulted in a significant increase in BAP and a significant decrease in OC in both groups (p<0.05). Zinc supplementation significantly elevated BAP levels (p<0.001) but did not prevent the decrease in OC levels. Conclusion: The findings of this study indicate that weightlessness significantly reduces bone formation (as measured by OC) regardless of zinc supplementation. Thus, the administration of zinc may not be sufficient to prevent bone resorption during long-term spaceflight. Further research is required to identify optimal strategies for maintaining bone health in weightless conditions.